Pathobiological Interactions of Local Bone Marrow Renin-Angiotensin System and Central Nervous System in Systemic Arterial Hypertension - Ciftciler, Rafiye; Haznedaroglu, Ibrahim Celalettin (Frontiers in Endocrinology, 2020)
Circulating renin-angiotensin system (RAS) and local paracrin-autocrin-intracrin tissue-based RAS participate in numerous pathobiological events. Pro-inflammatory, pro-fibrotic, and pro-thrombotic consequences associated with local RAS activation have been detected at cellular and molecular level. Regenerative progenitor cell therapy in response to RAS modulating pharmacotherapy has emerged as an adjunct in the context of endothelial cell injury and regeneration to improve regeneration of the vascular endothelium. Local hematopoietic bone marrow (BM) RAS symbolizes the place of cross-interaction between vascular biology and cellular events from embryogenesis to definitive hematopoiesis underlying vascular atherosclerosis. The BM microenvironment also contains Mas receptors, which control the proliferative role of Ang 1-7 on hematopoietic stem cells. Ang 1-7 is produced from Ang-II or Ang-I with the help of ACE2. Various tissues and organs also have an effect on the RAS system. The leukocytes contain and synthesize immunoreactive angiotensinogen species capable of producing angiotensin in the basal state or after incubation with renin. The significance of RAS employment in atherosclerosis and hypertension was indicated by novel bidirectional Central Nervous System (CNS) RAS–BM RAS communications. Myeloid cells generated within the context of hematopoietic BM RAS are considered as the initiators and decision shapers in atherosclerosis. Macrophages in the atherosclerotic lesions contain angiotensin peptides by which RAS blockers inhibit monocyte activation and adherence. Furthermore, vascular biology in relation to inflammation and neoplasia is also affected by local tissue RAS. The purpose of this article is to outline interactions of circulating and local angiotensin systems, especially local bone marrow RAS, in the vascular pathobiological microenvironment of CNS.